PkM. SMA NEGERI 2 ABIANSEMAL BADUNG DALAM MENINGKATKAN KAPASITAS PEMBELAJARAN KURIKULUM MERDEKA - I Komang Sukendra; Ida Ayu Agung Ekasiadi; Gde Iwan Setiawan (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
SMA Negeri 2 Abiansemal Badung is located at JL. Denpasar-Abiansemal, Medium, Abiansemal, Badung, Medium, District. Abiansemal, Kab. Badung, Bali with principal I Made Suwardana, S.Pd., M.Pd. In carrying out its activities, SMA Negeri 2 Abiansemal is under the auspices of the Ministry of Education and Culture. Based on the problems at SMA Negeri 2 Abiansemal Badung, the PkM Team at PGRI Mahadewa Indonesia University decided on priority problems that could be helped by Partners, namely human resource problems, school facilities and infrastructure for which solutions were immediately sought. The first problem is that teachers still experience problems in creating independent curriculum teaching modules, and the second problem is the lack of organization in school libraries in the era of digitalization, namely digital libraries. The implementation method is training and mentoring through the application of technology. The first activity concerns the problem of teachers' lack of knowledge in writing independent curriculum teaching modules. The activities were carried out in two stages, namely training activities in presenting materials related to writing in the creation of independent curriculum teaching modules. The mentoring activity for making teaching modules aims to improve teacher skills for making independent curriculum teaching modules. The second activity is a solution to the problem of poorly organized school libraries, namely digital libraries involving library staff. Partner participation in preparing training places, mentoring, and helping prepare food at school. After conducting training and mentoring, there was an increase in teachers in creating independent curriculum teaching modules and there was an increase in knowledge in the digital library at SMA Negeri 2 Abiansemal. The PkM results show that there has been an increase in teachers in creating independent curriculum teaching modules, and an increase in digital library knowledge skills.